Mitigating Suburban English Writing Teachers’ Constrained Professional Development Through Distance Education: One Case Study - Zhang, Xiaodong (International Review of Research in Open and Distributed Learning, 2018)
This study reports on how a Chinese suburban English writing teacher responded to systemic functional linguistics (SFL)-based distance education. The study draws on qualitative content analyses of the teacher’s reflections, interviews, and classroom interactions. The results show that through SFL-based distance education, the teacher, interacting with his agency, overcame multiple constraints and developed academically in terms of how to understand valued academic writing. Additionally, the teacher also harnessed this newfound knowledge to support students’ socialization into academic English discourse. The study concludes the effectiveness of SFL-based distance education for English writing teachers in similarly constrained contexts, which could be enhanced by teachers’ agency. Implications of the study include synergizing the SFL-based curriculum with distance teacher education so that language educators can better assist students in gaining the knowledge needed for navigating academic English literacy.